A review of the geochronology of the Margate Terrane reveals a history of diachronous terrane docking and arc accretion across the Mesoproterozoic Natal belt, southeastern Africa. (February 2019) - Mendonidis, P.; Thomas, R.J.
Abstract: The incremental accumulation of geochronological data from the Margate Terrane over the past two decades has progressively revealed a tectono-magmatic history of lengthening duration and greater complexity. The Margate Terrane is the southernmost of three Proterozoic island arc terranes that accreted against the southern margin of the Kaapvaal Craton which together form the Natal metamorphic belt. Early geochronological data suggested that the Margate Terrane was the youngest of the three terranes. Moreover, age bracketing of deformational fabrics indicated that the Margate Terrane was still tectonically active at ∼1040 Ma, some 90 Ma after the northernmost Tugela Terrane had been obducted onto the Kaapvaal Craton (∼1155 Ma) and had stabilised. More recent U-Pb zircon data show that the magmatic development of the Margate Terrane goes back as far as ∼1180 Ma, indicating that its protolith crust is not much younger than that of the Tugela or Mzumbe terranes. Nevertheless, age bracketing of tectonic fabrics indicates that there were two nearly coaxial tectonic events that affected the Margate and Mzumbe terranes, but not the Tugela Terrane which is thought to have escaped these events, having been shielded from them by the underlying rigid southern margin of the Kaapvaal Craton. Geochronology has revealed a marked southward younging of the earliest D1 event across the belt, manifested as southerly-dipping fabrics and associated with initiation of terrane accretion across the belt: D1 TUGELA  = ∼1200 Ma; D1 MZUMBE  = ∼1150 Ma and D1 MARGATE  = ∼1090 Ma. The youngest plutons and tectonic fabrics in the Margate and Mzumbe Terranes (∼1030–1040 Ma) are interpreted in terms of oblique collisional tectonics associated with the assembly of Rodinia. The geochronological data support correlation with events and lithologies in the Bushmanland Subprovince of the Namaqua metamorphic belt and the Vardeklettane Terrane of the Maud belt in westernmost Dronning Maud Land, East Antarctica. Highlights: Margate Terrane geochronological data reveal four magmatic events. Diachronous terrane docking and arc accretion occurred between 1170 Ma and 1040 Ma. Events are penecontemporaneous with similar ones in the Namaqua and Maud belts. Data suggest juxtapositioning of the Margate Terrane and Llano Belt at ∼1040 Ma.